2012
DOI: 10.1103/physrevb.85.035112
|View full text |Cite
|
Sign up to set email alerts
|

Single-layer terahertz metamaterials with bulk optical constants

Abstract: We investigate the conditions under which single layer metamaterials may be described by bulk optical constants. Terahertz time domain spectroscopy is utilized to investigate two types of geometries, both with two different sizes of embedding dielectric -cubic and tetragonal unit cells. The tetragonal metamaterials are shown to yield layer dependent optical constants, whereas the cubic metamaterials yielded layer independent optical constants. We establish guidelines for when ǫ and µ can be used as material pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
(32 reference statements)
1
17
0
Order By: Relevance
“…So far, both numerical [2][3][4][5] and experimental [6][7][8][9] techniques have been used to obtain the transmission and reflection coefficients for metamaterial slabs with a rather limited number of nanostructured layers. The coefficients obtained for such slabs do not necessarily describe the properties of a bulk metamaterial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, both numerical [2][3][4][5] and experimental [6][7][8][9] techniques have been used to obtain the transmission and reflection coefficients for metamaterial slabs with a rather limited number of nanostructured layers. The coefficients obtained for such slabs do not necessarily describe the properties of a bulk metamaterial.…”
mentioning
confidence: 99%
“…The coefficients obtained for such slabs do not necessarily describe the properties of a bulk metamaterial. One approach to characterize the material would be to successively increase the number of layers and see if the optical characteristics converge [3,4,9]. However, the understanding of the real physics that determines the final transmission properties is lost when using this procedure.…”
mentioning
confidence: 99%
“…However, we have observed that the zero-n gap edges can only be described in superlattices composed by alternating layers of LHM and a conventional dielectric [4], but this approximation does not remain valid for superlattices composed by two alternating dispersive media. According with recent advances in microstructuring material techniques and with the possibility to develop single-layer terahertz metamaterials [8], we expect that present results may be useful for applications in filters and reflectors.…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, the possibility to have the simultaneous existence of the zero-n and the zero-φ eff gaps in the same structure, operating at terahertz range, becomes of great importance for a wide range of applications, such as omnireflectors and optical filters. In fact, in the last two years, single-layer terahertz metamaterials were fabricated by means of the optical lithography technique [8], opening up the possibility to realize these metamaterial-polaritonic photonic superlattices with optical responses in the THz range.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were motivated by the new possibilities to manipulate the light propagation properties, opening routes for the design and development of new optical devices [15][16][17]. On the other hand, the advent of metamaterials [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33], which were first idealized by Veselago [18] as materials with simultaneous negative permittivity ε and negative permeability μ and, hence, a negative index of refraction n ε p μ p , has opened the possibility to obtain several new phenomena, such as the existence of the non-Bragg gaps, i.e., gaps with a physical origin completely different from the conventional Bragg scattering mechanism, which cannot be observed in superlattices composed by double positive (DPS) or conventional dielectric materials. In present days, there are several kinds of metamaterials which are commonly known as single negative electric (SNE), single negative magnetic (SNM), and double negative (DNG) metamaterials according to the signs of their electric and magnetic effective responses, respectively.…”
mentioning
confidence: 99%